Greenhouse Gas Emissions, Land Use, and Sustainable Natural Resource Management: A Review - Shreya Singh (International Journal of Sustainability, 2025)
Greenhouse gas (GHG) emissions, changes in land use, and the exploitation of natural resources are significant obstacles to achieving global sustainable development goals. These interconnected challenges have far-reaching implications for environmental stability, economic growth, and societal well-being.Urbanization, deforestation, and agriculture are examples of land use activities that significantly increase greenhouse gas emissions. Agricultural activities release methane and nitrous oxide, while deforestation leads to carbon dioxide emissions by reducing forest cover, a vital carbon sink. Urbanization and industrialization further exacerbate emissions through energy-intensive activities and infrastructure development. These practices not only contribute to global warming but also degrade ecosystems, reduce biodiversity, and compromise the availability of essential natural resources like water and fertile soil.Growing populations and economic demands have led to the unsustainable use of natural resources, which has degraded the environment and depleted supplies. Overextraction of minerals, excessive water use, and soil erosion are examples of how improper resource management can compromise long-term sustainability. These activities also intensify the impacts of climate change by altering natural processes and ecosystems. Addressing these issues requires a multi-faceted approach to sustainable natural resource management. Strategies such as promoting renewable energy, implementing carbon sequestration technologies, and adopting eco-friendly land use practices are essential. For instance, afforestation, conservation agriculture, and urban green spaces can help mitigate emissions and enhance environmental resilience. Additionally, integrating policy measures that prioritize resource efficiency, environmental conservation, and technological innovation is crucial for sustainable development. This review underscores the importance of adopting sustainable practices to mitigate the impacts of GHG emissions, land use changes, and resource exploitation. By aligning environmental and economic objectives, societies can progress toward achieving climate goals and securing a sustainable future for generations to come.
Keywords: Land use change; carbon sequestration; climate change mitigation; greenhouse gas emissions; natural resources; sustainable development